2018
DOI: 10.1111/inm.12475
|View full text |Cite
|
Sign up to set email alerts
|

The underreporting of medication errors: A retrospective and comparative root cause analysis in an acute mental health unit over a 3‐year period

Abstract: Medication errors remain a commonly reported clinical incident in health care as highlighted by the World Health Organization's focus to reduce medication-related harm. This retrospective quantitative analysis examined medication errors reported by staff using an electronic Clinical Incident Management System (CIMS) during a 3-year period from April 2014 to April 2017 at a metropolitan mental health ward in Western Australia. The aim of the project was to identify types of medication errors and the context in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This is in accordance with other studies [26,27]. However, the reverse was reported in other published data [28]. The increased negative score of the teamwork across the unit is the expected image for the lower scores of communication and patients transition items of the questionnaire.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with other studies [26,27]. However, the reverse was reported in other published data [28]. The increased negative score of the teamwork across the unit is the expected image for the lower scores of communication and patients transition items of the questionnaire.…”
Section: Discussionsupporting
confidence: 93%
“…To be valid, all medication errors have to be identified and promptly reported. There is accumulated evidence of widespread and significant under-reporting of medication errors by healthcare profession [25][26][27][28][29][30][31][32]. A recent mixed methods study conducted in Qatar identified a number of barriers to error reporting including fear and worry,that submitting was likely to lead to further investigation,concerns over the impact on working relationships,and the potential lack of confidentiality [16].…”
Section: Discussionmentioning
confidence: 99%
“… 11 However, the percentages of the errors that occur in the various stages are different. 1 , 4 , 12 Healthcare professionals (HCPs) should be focused on their knowledge, attitudes, and practices toward medication errors and reporting them. 13 , 14 Having a medication error reporting system is necessary for assessing and minimizing medication errors, which, in turn, protects patients from harm.…”
Section: Introductionmentioning
confidence: 99%